2006
DOI: 10.7326/0003-4819-144-12-200606200-00003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Abatacept in Patients with Methotrexate-Resistant Active Rheumatoid Arthritis

Abstract: Abatacept statistically significantly reduced disease activity in patients with rheumatoid arthritis and an inadequate response to methotrexate. Longer treatment in different patient populations is needed to establish its appropriate role in rheumatoid arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
416
1
20

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 659 publications
(470 citation statements)
references
References 24 publications
28
416
1
20
Order By: Relevance
“…However, the remission rates of these non-TNF biologic agents in anti-TNF-naïve or -refractory populations differ. For abatacept, the remission rate in MTX-resistant patients (AIM study) was 14.8% [28], while that in anti-TNF therapy-refractory patients (ATTAIN study) was 10.0% [29]. In the case of rituximab, the American College of Rheumatology (ACR) 70% rate in MTX-resistant patients (DANCER study) was 20% [30], and that in anti-TNF therapy-refractory patients (REFLEX study) was 12% [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, the remission rates of these non-TNF biologic agents in anti-TNF-naïve or -refractory populations differ. For abatacept, the remission rate in MTX-resistant patients (AIM study) was 14.8% [28], while that in anti-TNF therapy-refractory patients (ATTAIN study) was 10.0% [29]. In the case of rituximab, the American College of Rheumatology (ACR) 70% rate in MTX-resistant patients (DANCER study) was 20% [30], and that in anti-TNF therapy-refractory patients (REFLEX study) was 12% [31].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the 30-min intravenous abatacept infusion was well tolerated by patients in this trial [29] and did not require premedication [37]. The incidence of infusion reactions was low, reported by only 5% of abatacept-treated patients compared with 3% of the placebo-treated patients ( p= 0.35), and no severe or very severe reactions were observed in either group during the double-blind period.…”
Section: Safety Of Abatacept In the Attain Trialmentioning
confidence: 70%
“…As in AMPLE, these 3 abatacept studies included patients with an inadequate response to MTX who were biologics‐naive 5, 24, 25, 26.…”
Section: Discussionmentioning
confidence: 99%
“…Abatacept is a T‐cell costimulation modulator that has shown efficacy in patients with RA in a wide range of disease and treatment durations 4, 5, 6, 7, 8, 9, 10, 11. The AMPLE (Abatacept versus Adalimumab Comparison in Biologic‐Naive RA Subjects with Background MTX) trial, the first head‐to‐head trial comparing biologic DMARDs in patients with RA receiving MTX, demonstrated noninferiority for abatacept versus adalimumab by the ACR 20% improvement response (ACR20) at year 1 (64.8% subcutaneous [SC] abatacept versus 63.4% adalimumab; estimated difference between treatments 1.8% [95% confidence interval (95% CI) −5.6, 9.2] in an intent‐to‐treat analysis) 12.…”
Section: Introductionmentioning
confidence: 99%